X-Ray Diffraction Studies of Some Polyatomic Cations in the Solid and Liquid State - Crump, David B. (My University, 1970)
In a study of the structures of some polyatomic cations of Group VI and VII, the compound Se4(HS2O7)2 has been prepared and its structure determined by single crystal X-ray diffraction. The bonding in the square planar cation has been discussed in terms of molecular orbital and valence bond theory. The anion geometry has been discussed and simple rules proposed to predict the changes which occur in bond length and bond angle when one or more oxygen in an SO4 tetrahedron is bonded to another atom or group.
A θ/θ vertical diffractometer has been constructed, and computer programmes written, so that cation structures could be determined in solution. The structures of the Se4 2+ and Te4 2+ cations have been determined in fluorosulphuric acid, and are shown to be square planar.
Liquid diffraction studies of 3:1, I2/S2O6F2 solutions have shown the presence of a cation containing a linear chain of three iodine atoms.
Keywords: polyatomic, cations, X-ray, diffraction, molecular, bond, solid, liquid